Analysis of lncRNA sequences: FAM3D-AS1, LINC01230, LINC01315 and LINC01468 in endometrial cancer - Jan Bieńkiewicz; Hanna Romanowicz; Bożena Szymańska; Daria Domańska-Senderowska; Miłosz Wilczyński; Anna Stepowicz; Andrzej Malinowski; Beata Smolarz (BMC Cancer, 2022)
Abstract Background The analysis of long non-coding RNA (lncRNA) in endometrial cancer is a novel field of science. Although numerous lncRNA sequences have been identified until today, their correlation with endometrial cancer is still undetermined. The aim of this study was to analyze the expression of four lncRNA sequences: FAM3D-AS1, LINC01230, LINC01315 and LINC01468 and to investigate their significance in endometrial cancer. Methods LncRNA sequences were investigated in paraffin blocks (tumor tissue and non-malignant endometrial tissue in archival postoperative specimens) in endometrial cancer patients (Cases, n = 120) and in cancer-free controls (n = 80) using real-time PCR assay. Results This study revealed a lower expression of LINC01468 in endometrial cancer patients than in controls. Both LINC01468 and FAM3D-AS1 were positively correlated with Body Mass Index (BMI) in cancer-free controls. Conclusions LncRNA LINC01468 may be a protective factor in development of endometrial cancer.